Photoelectric conversion element, photoelectric conversion device, method for detecting light, and method for manufacturing photoelectric conversion element

By adopting a multi-layer structure of perovskite structure, inorganic transition metal and organic ligand in the photoelectric conversion element, the problems of large environmental load and insufficient responsiveness during weak light signal processing in the prior art are solved, and photoelectric conversion with high efficiency and high sensitivity is achieved.

CN119732213APending Publication Date: 2025-03-28THE JAPAN SCI & TECH AGENCY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380059824.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-19
Filing Date
2023-07-31
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

When existing photoelectric conversion elements process weak light signals, the environmental load is large and the responsiveness is insufficient, making it difficult to achieve high efficiency and high sensitivity photoelectric conversion.

Method used

Using a multi-layer structure photoelectric conversion element composed of a perovskite structure, an inorganic transition metal and an organic ligand, an energy level structure is optimized to improve the photoelectric conversion efficiency by forming a 1-to-1 layer arrangement between the perovskite structure and the inorganic transition metal and forming an organic metal complex layer between the inorganic transition metal and the organic ligand.

Benefits of technology

It realizes efficient conversion of weak light signals under low ambient load, significantly improving the response speed and sensitivity of the photoelectric conversion element.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119732213A_ABST
    Figure CN119732213A_ABST
Patent Text Reader

Abstract

The photoelectric conversion element (100) comprises, in order as a photoelectric conversion layer (103): a first layer (104) comprising a plurality of particles containing a perovskite structure (201) as a main component, or an aggregate or a thin film thereof; a second layer (105) comprising a plurality of particles containing an inorganic transition metal (205) as a main component, or an aggregate or a thin film thereof; and a third layer (106) comprising a plurality of particles containing an organic ligand (206) as a main component, or an aggregate or a thin film thereof, the inorganic transition metal (205) in the second layer (105) being different from the central metal contained in the perovskite structure (201), and the inorganic transition metal (205) being a metal oxide at a boundary surface (S1) between the first layer (104) and the second layer (105), and the inorganic transition metal (205) being a metal oxide at a boundary surface (S2) between the first layer (104) and the second layer (105). The perovskite structure (201) and the inorganic transition metal (205) of the second layer (105) form a one-to-one layer arrangement, and the inorganic transition metal (205) of the second layer (105) and the organic ligand (206) of the third layer (106) form an organic metal complex layer (108) obtained from an organic metal complex (208) together at a boundary surface (S2) between the second layer (105) and the third layer (106).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a photoelectric conversion element, a photoelectric conversion device, a light detection method, and a method for manufacturing a photoelectric conversion element. This application claims priority based on Japanese Patent Application No. 2022-130971 filed in Japan on August 19, 2022, and the contents are incorporated herein by reference. Background Art

[0002] It is known that a technology for amplifying photocurrent using photoelectric conversion elements such as avalanche photodiodes and photomultiplier tubes is used. Avalanche photodiodes are photodiodes that amplify photocurrent by irradiating light between pn junctions formed by inorganic semiconductors in a state where a reverse voltage is applied, thereby repeatedly performing collisions between generated electrons and holes and a lattice, and generating electrons and holes from the collided lattice in a chain reaction. A photomultiplier tube is composed of a plurality of dynodes (Japanese: ダイノード) and a vacuum tube built therein, and by irradiating light to one dynode, the collisions between generated electrons and the dynode, and the generation of electrons from the collided dynode are repeatedly performed in a chain reaction, thereby amplifying photocurrent.

[0003] Patent document 1 discloses a photoelectric conversion element, which is stacked in sequence: a first layer, composed of multiple particles or their aggregates or thin films containing an inorganic semiconductor as a main component; a second layer, on the surface of the aforementioned particles or their aggregates, composed of multiple particles or their aggregates or thin films containing a perovskite structure as a main component; and a third layer, composed of multiple particles or their aggregates or thin films containing an organic metal complex as a main component, in the conduction band, the energy level of the aforementioned second layer is higher than the energy level of the aforementioned first layer, and the energy level of the aforementioned third layer is higher than the energy level of the aforementioned second layer, and the energy level of the aforementioned second layer in the valence band is higher than the energy level of the aforementioned third layer. Prior art literature Patent Literature

[0004] Patent Document 1: International Publication No. 2020 / 162317 Summary of the invention Problems to be solved by the invention

[0005] A photoelectric conversion element that is highly efficient and highly sensitive while suppressing environmental load to a weak optical signal and has superior responsiveness to that of the photoelectric conversion element of Patent Document 1 is desired.

[0006] The present invention is made in view of the above-mentioned situation, and its purpose is to provide a photoelectric conversion element, a photoelectric conversion device, a light detection method, and a method for manufacturing a photoelectric conversion element that are highly efficient, highly sensitive, and have better responsiveness for weak light signals while suppressing the environmental load to a lower level. Means for solving problems

[0007] In order to solve the above-mentioned problems, the present invention proposes the following means. (1) The photoelectric conversion element according to the first aspect of the present invention includes, as a photoelectric conversion layer, the following components in order: A first layer composed of a plurality of particles containing a perovskite structure as a main component, or an aggregate or a thin film thereof; A second layer composed of a plurality of particles containing an inorganic transition metal as a main component, or an aggregate or a thin film thereof; and The third layer is composed of a plurality of particles or aggregates or thin films containing an organic ligand as a main component, The inorganic transition metal of the second layer is different from the central metal contained in the perovskite structure. At the interface between the first layer and the second layer, the perovskite structure and the inorganic transition metal in the second layer form a one-to-one layer arrangement, At the interface between the second layer and the third layer, the inorganic transition metal in the second layer and the organic ligand in the third layer form an organic metal complex layer obtained from an organic metal complex. (2) According to Embodiment 2 of the present invention, in the photoelectric conversion element of Embodiment 1, In the conduction band, the LUMO energy level of the conduction band of the aforementioned organic metal complex layer is higher than the energy level of the conduction band of the aforementioned first layer, and In the valence band, the energy level of the valence band of the first layer is higher than the HOMO energy level of the valence band of the organic metal complex layer. (3) According to Embodiment 3 of the present invention, in the photoelectric conversion element of Embodiment 1 or Embodiment 2, The second layer may be a layer in which the inorganic transition metal is segregated on the surface of the first layer. (4) According to Embodiment 4 of the present invention, in the photoelectric conversion element according to any one of Embodiments 1 to 3, The second layer may be a single atomic layer of the inorganic transition metal. (5) According to aspect 5 of the present invention, in the photoelectric conversion element according to any one of aspects 1 to 4, The aforementioned organic ligand may be α-methylbenzylamine or terpyridine. (6) According to Embodiment 6 of the present invention, in the photoelectric conversion element according to any one of Embodiments 1 to 5, It may be that the central metal contained in the perovskite structure is lead, the inorganic transition metal of the second layer is europium, the inorganic transition metal of the second layer constituting the organic metal complex is europium, and the organic ligand constituting the organic metal complex is α-methylbenzylamine or terpyridine. (7) According to aspect 7 of the present invention, in the photoelectric conversion element according to any one of aspects 1 to 6, The aforementioned perovskite structure may be a compound represented by the formula CH3NH3PbI3. (8) In the photoelectric conversion device according to Embodiment 8 of the present invention, The photoelectric conversion element of embodiment 1 includes: A negative electrode layer is stacked on the opposite side of the second layer via the first layer, and A photoelectric conversion element in which a positive electrode layer is stacked on the opposite side of the second layer via the third layer. (9) The light detection method of aspect 9 of the present invention includes the following steps: In the photoelectric conversion device of embodiment 8, the photoelectric conversion layer receives visible light and / or near-infrared light, thereby causing current to flow between the negative electrode layer and the positive electrode layer. By measuring the electric current, the visible light and / or the near-infrared light is detected. (10) A method for manufacturing a photoelectric conversion element according to aspect 10 of the present invention includes: A first step is to coat the surface of the substrate with a mixture, the mixture comprising a raw material for a perovskite structure and an inorganic transition metal different from a central metal contained in the raw material for the perovskite structure and in the perovskite structure; A second step, after the first step, by forming a one-to-one layer arrangement between the perovskite structure and the inorganic transition metal, thereby forming a first layer consisting of a plurality of particles or aggregates or thin films containing the perovskite structure as a main component, and a second layer consisting of a plurality of particles or aggregates or thin films containing the inorganic transition metal as a main component; and In the third step, after the second step, an organic ligand is coordinated and bonded to the inorganic transition metal on the second surface of the second layer opposite to the surface in contact with the first layer, thereby forming an organic metal complex layer obtained from the organic metal complex. (11) According to Embodiment 11 of the present invention, in the method for manufacturing a photoelectric conversion element according to Embodiment 10, the method may include: In the conduction band, the LUMO energy level of the aforementioned organic metal complex layer is higher than the energy level of the conduction band of the aforementioned first layer, and In the valence band, the energy level of the valence band of the first layer is higher than the HOMO energy level of the organic metal complex layer. (12) According to Embodiment 12 of the present invention, in the method for manufacturing a photoelectric conversion element according to Embodiment 10 or Embodiment 11, In the second step, the second layer may be formed by segregating the inorganic transition metal on the surface of the first layer. (13) According to Embodiment 13 of the present invention, in the method for producing a photoelectric conversion element according to any one of Embodiments 10 to 12, the second layer may be a monoatomic layer of the inorganic transition metal. (14) A method for manufacturing a photoelectric conversion element according to aspect 14 of the present invention includes: a mixing step of mixing a raw material for a perovskite structure and an inorganic transition metal different from a central metal contained in the raw material for the perovskite structure and in the perovskite structure, thereby obtaining a mixture; A coating step of coating the surface of the substrate with the mixture to form a coating layer; A heating step of heating the coating layer after the coating step to form a first layer composed of a plurality of particles or aggregates or thin films containing the perovskite structure as a main component, and a second layer composed of a plurality of particles or aggregates or thin films containing the inorganic transition metal as a main component; and After the heating step, a step of applying a solution containing an organic ligand on the surface of the second layer opposite to the surface in contact with the first layer. Effects of the Invention

[0008] According to the above-mentioned aspects of the present invention, it is possible to provide a photoelectric conversion element, a photoelectric conversion device, a light detection method, and a method for manufacturing a photoelectric conversion element that are highly efficient, highly sensitive, and have better responsiveness to weak light signals while suppressing environmental load. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] [ Figure 1 ] is a cross-sectional view of a photoelectric conversion element involved in one embodiment of the present invention. [ Figure 2 ]for Figure 1 A cross-sectional view of an example of a method for manufacturing a photoelectric conversion element. [ Figure 3 ] shows Figure 1 Energy band structure of each layer of the photoelectric conversion element during operation. [ Figure 4 ] is a graph showing the response speed of the photocurrent obtained in the photoelectric conversion element involved in Example 1 of the present invention. [ Figure 5 ] is a graph showing the relationship between the concentration of Eu and the surface potential during light irradiation. The upper layer in the figure shows the experimental results in the "light irradiated" test area, while the lower layer in the figure shows the experimental results in the "no light irradiated" control test area. In addition, the right side of the potential image at each concentration of Eu shows the potential level bar (lower limit 0.2V to upper limit 0.5V) shown in shades. DETAILED DESCRIPTION

[0010] Hereinafter, the photoelectric conversion element, the photoelectric conversion device, the light detection method, and the manufacturing method of the photoelectric conversion element to which the embodiments of the present invention are applicable are described in detail using the accompanying drawings. It should be noted that, with respect to the accompanying drawings used in the following description, in order to make the features easy to understand, for the sake of convenience, the parts that are features are sometimes enlarged and shown, and the size ratios of the various components are not limited to being the same as the actual ones. In addition, the materials, dimensions, etc. exemplified in the following description are examples, and the present invention is not limited thereto, and can be implemented by appropriately changing within the scope of not changing its purpose.

[0011] (Photoelectric conversion element) Figure 1 1 is a cross-sectional view schematically showing the structure of a photoelectric conversion element 100 according to one embodiment of the present invention. The photoelectric conversion element 100 includes a positive electrode layer (positive electrode member) 101, a negative electrode layer (negative electrode member) 102, and a photoelectric conversion layer 103 located between the positive electrode layer 101 and the negative electrode layer 102. In the photoelectric conversion element 100, the negative electrode layer 102 is stacked on the opposite side of the second layer 105 via the first layer 104. In addition, in the photoelectric conversion element 100, the positive electrode layer 101 is stacked on the opposite side of the second layer 105 via the third layer 106.

[0012] As for the positive electrode layer (positive electrode component) 101 or the negative electrode layer (negative electrode component) 102, in the case of the side used to transmit light, it is preferable to use a light-transmitting material (i.e., a transparent or translucent electrode material). As electrode materials for these electrode layers, conductive metal oxide films, translucent metal films, etc. can be cited. Specifically, for example, the following films can be used: films made of conductive materials such as indium oxide, zinc oxide, tin oxide, and tin-doped indium oxide (indium tin oxide) (ITO), indium zinc oxide (IZO), NESA, etc. as their composites; films made of gold, platinum, silver, copper, etc. Among these electrode materials, ITO, indium zinc oxide, and tin oxide are preferred. As methods for making electrodes, vacuum evaporation, sputtering, ion plating, electroplating, etc. can be cited. In addition, as electrode materials, organic transparent conductive films such as polyaniline and its derivatives, polythiophene and its derivatives can also be used.

[0013] The other electrode that does not need to allow light to pass through may be opaque. As the electrode material of the other electrode, metals, conductive polymers, etc. can be used. Specific examples of electrode materials include metals (first metals) such as aluminum (Al) and zinc (Zn), and alloys of two or more of them; or alloys of one or more of the aforementioned first metals and one or more metals selected from the group consisting of gold (Au), silver (Ag), platinum (Pt), copper (Cu), manganese (Mn), titanium (Ti), cobalt (Co), nickel (Ni), tungsten (W) and tin (Sn); graphite; graphite intercalation compounds; polyaniline; conductive polymers such as polythiophene. As alloys, for example, magnesium-silver alloys, magnesium-indium alloys, magnesium-aluminum alloys, indium-silver alloys, lithium-aluminum alloys, lithium-magnesium alloys, lithium-indium alloys, calcium-aluminum alloys, etc. can be mentioned.

[0014] In order to guide light into the photoelectric conversion layer 103, the negative electrode layer 102 is preferably composed of a light-transmitting material, such as antimony-doped tin oxide (ATO), tin-doped indium oxide (ITO), zinc oxide, tin oxide, fluorine-doped tin oxide (FTO), etc. Since heat treatment is required in the manufacturing process of the photoelectric conversion element 100 of this embodiment, ATO having heat resistance is preferably used as the material of the negative electrode layer 102 among the above materials.

[0015] like Figure 1 As shown, the photoelectric conversion layer 103 involved in this embodiment includes: a first layer 104, which is composed of a plurality of particles or aggregates or thin films containing a perovskite structure 201 as a main component; a second layer 105, which is composed of a plurality of particles or aggregates or thin films containing an inorganic transition metal 205 different from the central metal contained in the perovskite structure 201 as a main component; and a third layer 106, which is composed of a plurality of particles or aggregates or thin films containing an organic ligand 206 as a main component. In the photoelectric conversion element 100, a positive electrode layer 101, a third layer 106, a second layer 105, a first layer 104, and a negative electrode layer 102 are stacked in order. Here, an organic metal complex layer 108 is formed by the second layer 105 and the third layer 106. It is preferable to form the photoelectric conversion layer 103 in a manner that forms a conductive path from the positive electrode layer 101 to the negative electrode layer 102. The more conductive paths formed, the better. It should be noted that the “layer” in the present embodiment refers to a film formed by one or more film forming processes, is not limited to a flat layer, and may not be integral.

[0016] In the photoelectric conversion layer 103, the materials and compositions of the first layer 104 and the organic metal complex layer 108 are preferably determined so that the organic metal complex layer 108 has a higher energy level than the first layer 104 in terms of the conduction band (Lowest Unoccupied Molecular Orbital (LUMO), excited state), and the first layer 104 has a higher energy level than the organic metal complex layer 108 in terms of the valence band (Highest Occupied Molecular Orbital (HOMO), ground state). In the conduction band, the LUMO energy level of the conduction band of the organic metal complex layer 108 is higher than the energy level of the conduction band of the first layer 104. For example, the energy level of the valence band of the first layer 104 can be set to be -5.5 eV or higher, and the energy level of the conduction band can be set to be -3 eV or lower. In addition, with respect to the organic metal complex layer 108 (preferably, for example, ions of an inorganic transition metal 205), it is preferred that the HOMO energy level of the valence band is greater than -6 eV and the LUMO energy level of the conduction band is less than -2 eV. As a method for measuring the energy level, for example, UPS (ultraviolet photoelectron spectroscopy) in a vacuum or in an atmospheric atmosphere may be used. In addition, depending on the circumstances, energy level values ​​published in the literature may be used instead.

[0017] It should be noted that the photoelectric conversion layer 103 involved in this embodiment can include in sequence: an inorganic semiconductor layer 107 containing an inorganic semiconductor as a main component; a first layer 104 composed of a plurality of particles or aggregates or thin films containing a perovskite structure 201 as a main component; a second layer 105 composed of a plurality of particles or aggregates or thin films containing an inorganic transition metal 205 different from the central metal contained in the perovskite structure 201 as a main component; and a third layer 106 composed of a plurality of particles or aggregates or thin films containing an organic ligand 206 as a main component.

[0018] (When the inorganic semiconductor layer 107 is present) When the inorganic semiconductor layer 107 is present, the inorganic semiconductor layer 107 is provided on the negative electrode layer 102. The form of the inorganic semiconductor layer 107 is not particularly limited. As for the form of the inorganic semiconductor layer 107, for example, it is a porous film obtained from an aggregate of a plurality of particles and having a plurality of gaps between the particles. When the inorganic semiconductor layer 107 is obtained from particles, the particles in contact with the first layer 104 are preferably in contact with the negative electrode layer 102 directly or indirectly via other particles in a manner electrically connected to the negative electrode layer 102.

[0019] The inorganic semiconductor contained in the inorganic semiconductor layer 107 is preferably an inorganic semiconductor having an absorption wavelength within the ultraviolet region, for example, titanium oxide, zinc oxide, etc. The thickness of the first layer 104 is preferably about 10 nm to 1000 nm, and more preferably about 50 nm to 500 nm. The inorganic semiconductor layer 107 may be composed only of an inorganic semiconductor.

[0020] (First floor 104) The first layer 104 is composed of a plurality of particles or aggregates thereof or thin films containing the perovskite structure 201 as a main component. As the form of the first layer 104, a thin film is preferred. The content of the perovskite structure 201 in the first layer 104 is 60% by mass or more relative to the total mass of the first layer 104. A more preferred content of the perovskite structure 201 is 80% by mass or more. The first layer 104 can be composed only of the perovskite structure 201, so the upper limit of the content of the perovskite structure 201 is 100% by mass.

[0021] The perovskite structure 201 constituting the first layer 104 is, for example, a compound ABX3 composed of three ions A, B, and X. In order to segregate the inorganic transition metal 205 different from the central metal contained in the perovskite structure 201, the perovskite structure 201 is preferably an inorganic perovskite compound. Specifically, the ions B and X form a plurality of unit cells (BX6) having an octahedral structure. 4- , and the octahedral structures of adjacent unit units share one face. Ion B is arranged at the center of the octahedron, and ion X is arranged at the vertex of the octahedron. Among them, the central metal becomes ion B arranged at the center of the octahedron. In addition, ion A is arranged at a position circumscribed to the octahedral structure of each unit unit. Ion A is, for example, Cs + , K + , Rb + Metal cations, CH3NH3 + (MA), NH=CHNH2 + (FA) and other organic cations. Ion B is lead ion (Pb 2+ ), tin ions (Sn 2+ ). X is 1 - , Cl - Br - The size and shape of the band gap can be changed by using ions selected from ions A, B, and X. When tin is added to the perovskite structure 201, the band gap becomes narrower, and the responsiveness to long-wavelength light such as near-infrared light can be improved.

[0022] In addition, it is preferred that the energy level of the valence band of the first layer 104 is higher than the HOMO energy level of the valence band of the organic metal complex layer 108 and is intermittently connected to the HOMO energy level. As the composition of the first layer 104 (perovskite structure) that satisfies these conditions, for example, CsPbX3 (X = Br or I), CH3NH3PbI3, etc. can be cited.

[0023] The thickness of the first layer 104 is not particularly limited, but for example, the thickness of the first layer 104 is 1 to 10 nm.

[0024] The second layer 105 is preferably a layer in which the inorganic transition metal 205 is segregated on the surface of the first layer 104 in a manner that is directly bonded to the perovskite structure of the first layer 104. In addition, the second layer 105 is preferably a monoatomic layer of the inorganic transition metal 205. The content of the inorganic transition metal 205 in the second layer 105 is 60% by mass or more relative to the total mass of the second layer 105. The more preferred content of the inorganic transition metal 205 is 80% by mass or more. The second layer 105 can be composed only of the inorganic transition metal 205, so the upper limit of the content of the inorganic transition metal 205 is 100% by mass. The inorganic transition metal 205 is preferably a metal cation. As the metal cation, for example, Eu having a reduction level of LUMO can be cited. 3+ Cr 3+ etc., Ru with oxidation level HOMO 2+ , Fe 2+ , Mn 2+ 、Co 2+ etc. Eu is particularly preferred 3+ The inorganic transition metal 205 of the second layer 105 is different from the central metal (ion B) contained in the first layer 104. By making the inorganic transition metal 205 of the second layer 105 different from the central metal contained in the perovskite structure 201 different from the metal contained in the first layer 104, the hole capture efficiency can be further improved, and the response speed of the photoelectric conversion element 100 can be improved.

[0025] The third layer 106 is disposed on the second layer 105 in contact. In order to achieve amplification of the photocurrent, the organic metal complex 208 is preferably bonded to the molecules of the perovskite structure in a current path from the positive electrode layer 101 side toward the second layer 105 side in a manner that the organic ligand 206 and the inorganic transition metal ions 205 different from the central metal contained in the perovskite structure 201 are arranged in the order. That is, the organic metal complex layer 108 can be divided into the second layer 105 obtained from the inorganic transition metal ions and the third layer 106 obtained from the organic ligand ions. The third layer 106 is preferably a monomolecular layer of the organic ligand 206. The content of the organic ligand 206 in the third layer 106 is 60% by mass or more relative to the total mass of the third layer 106. The more preferred content of the organic ligand 206 is 80% by mass or more. The third layer 106 can be composed only of the organic ligand 206, so the upper limit of the content of the organic ligand 206 is 100% by mass. In addition, the boundary between these two layers may be confirmed using, for example, a transmission electron microscope (TEM) or the like.

[0026] As the organic ligand 206 here, there can be mentioned ligands of common metal complexes, for example, (i) organic compounds having carboxyl, nitro, sulfonic, phosphoric, hydroxyl, oxo, amino, etc.; (ii) ethylenediamine derivatives; (iii) organic ligands containing heterocyclic atoms such as terpyridine derivatives, phenanthroline derivatives, and bipyridine derivatives; (iv) acetylacetone-based organic ligands such as catechol derivatives, quinone derivatives, naphthoic acid derivatives, and acetylacetone derivatives (specifically, for example, acetylacetone) (here, "acetylacetone-based organic ligand" refers to an organic ligand that can coordinately bond with multiple transition metal ions (for example, while forming a six-membered ring) via two oxygen atoms) and the like. It should be noted that the terpyridine derivative has a structure represented by the following formula (1). As the organic ligand 206, α-methylbenzylamine or terpyridine is preferred. α-Methylbenzylamine has a structure represented by the following formula (2).

[0027] [Chemical formula 1]

[0028] [Chemical formula 2]

[0029] In the photoelectric conversion element 100, the perovskite structure 201 and the inorganic transition metal 205 of the second layer 105 which is different from the central metal contained in the perovskite structure 201 form a one-to-one layer arrangement at the interface S1 between the first layer 104 and the second layer 105. Here, "the perovskite structure 201 and the inorganic transition metal 205 of the second layer 105 which is different from the central metal contained in the perovskite structure 201 form a one-to-one layer arrangement at the interface S1 between the first layer 104 and the second layer 105" means that at the interface S1 between the first layer 104 and the second layer 105, at a position circumscribing the octahedral structure of the unit unit constituting the perovskite structure 201, one atom of the inorganic transition metal 205 which is different from the central metal contained in the perovskite structure 201 is arranged relative to one octahedral structure. By forming a one-to-one layer arrangement of the perovskite structure 201 and the inorganic transition metal 205 of the second layer 105 which is different from the central metal contained in the perovskite structure 201 at the interface S1 between the first layer 104 and the second layer 105, it is possible to more effectively capture holes in a uniform manner. Thus, the response speed of the photoelectric conversion element 100 can be improved.

[0030] Confirmation that the perovskite structure 201 and the inorganic transition metal 205 of the second layer 105, which is different from the central metal contained in the perovskite structure 201, form a one-to-one layer arrangement at the boundary surface S1 between the first layer 104 and the second layer 105 can be performed, for example, by observing the cross section of the photoelectric conversion element 100 using a SEM or measuring the surface potential using a scanning probe microscope.

[0031] Among them, scanning probe microscopy is generally a method for observing the surface shape and surface structure of a sample. For example, in addition to observing the surface shape of the sample (i.e., obtaining height information), other physical property information of the sample surface such as current, potential, hardness, and viscoelasticity is measured. Then, analysis such as texture display and 3D cross-sectional shape analysis function for superimposing and displaying the aforementioned other physical property information with the aforementioned height information is performed. Based on the obtained image, the presence, state, properties and influence of coordination bonds can be evaluated. In the above manner, the charge state of the surface of the obtained sample is understood, and the existence and condition of the coordination bond between the perovskite structure 201 and the inorganic transition metal 205 are studied, thereby indirectly confirming that at the position circumscribed to the octahedral structure of the unit unit constituting the perovskite structure 201, the aforementioned perovskite structure 201 and the inorganic transition metal 205 form a one-to-one layer arrangement. In addition, the atomic force microscope is also a method for observing the surface shape of a sample, and can measure the distance between atoms, so it is possible to observe the change in the distance between the perovskite structure 201 and the inorganic transition metal 205, thereby indirectly confirming that the perovskite structure 201 and the inorganic transition metal 205 form a 1:1 layer arrangement at a position circumscribed to the octahedral structure of the unit unit constituting the perovskite structure 201. In addition, as in the case of the scanning probe microscope described above, by using a cantilever having conductivity and magnetism, the electric field force (electric field gradient force) and the magnetic image are observed simultaneously with the surface shape image, thereby also being able to evaluate the presence, state, nature and influence of coordination bonds based on the obtained image. Other methods include optical methods (for example, methods of detecting optical changes caused by intramolecular electron transitions in coordination bonds used to form a one-to-one layer arrangement using spectroscopy through absorption and scattering of light), magnetic methods (for example, methods of detecting magnetic changes caused by changes in the spin state of transition metal ions using electron magnetic resonance), etc.

[0032] In the photoelectric conversion element 100, at the boundary surface S2 between the second layer 105 and the third layer 106, the inorganic transition metal 205 of the second layer 105, which is different from the central metal contained in the perovskite structure 201, and the organic ligand 206 of the third layer 106 form an organic metal complex layer 108 obtained from an organic metal complex 208. By forming the organic metal complex layer 108 obtained from the organic metal complex 208 together with the inorganic transition metal 205 and the organic ligand 206 of the third layer 106, the photocurrent of the photoelectric conversion element 100 can be efficiently amplified even for a weak light signal.

[0033] Regarding the confirmation of the organic metal complex layer 108 obtained by forming an organic metal complex 208 together with the inorganic transition metal 205 of the second layer 105 which is different from the central metal contained in the perovskite structure 201 and the organic ligand 206 of the third layer 106 at the boundary surface S2 between the second layer 105 and the third layer 106 in the photoelectric conversion element 100, it can be carried out, for example, by X-ray photoelectron spectroscopy (XPS) or infrared spectroscopy (FT-IR).

[0034] When the photoelectric conversion element 100 of this embodiment is applied to a photosensor, the photoelectric conversion element 100 is mounted on a semiconductor substrate such as silicon or a glass substrate. In this case, for example, the following device configurations can be mentioned. (1) A method in which the transparent negative electrode layer 102 is formed on the uppermost layer farthest from the semiconductor substrate (i.e., a structure in which, from the uppermost layer on the light-entering side, the layers are stacked in the order of (transparent) negative electrode layer 102 / first layer 104 / organic metal complex layer 108 / positive electrode layer 101 / (Si) substrate); (2) A method in which the positive electrode layer 101 having transparency is formed on the uppermost layer farthest from the semiconductor substrate (i.e., a structure in which, from the uppermost layer on the light-entering side, the layers are stacked in the order of (transparent) positive electrode layer 101 / organic metal complex layer 108 / first layer 104 / negative electrode layer 102 / (Si) substrate); (3) A transparent negative electrode layer 102 is formed adjacent to the glass substrate (i.e., a structure in which, from the uppermost layer on the light-incident side, the layers are stacked in the order of (glass) substrate / negative electrode layer 102 / first layer 104 / organic metal complex layer 108 / positive electrode layer 101); In addition, as another device configuration, in the device configurations (1) to (3) described above, a configuration in which the inorganic semiconductor 107 is present between the (transparent) negative electrode layer 102 and the first layer 104 can be cited.

[0035] In the photoelectric conversion element 100, preferably, the central metal contained in the perovskite structure 201 is lead, the inorganic transition metal 205 of the second layer 105 is europium, the inorganic transition metal of the second layer 105 constituting the organic metal complex 208 is europium, and the organic ligand 206 constituting the organic metal complex 208 is α-methylbenzylamine or terpyridine.

[0036] (Method of Manufacturing Photoelectric Conversion Element 100) Figure 2 (a) to (f) are cross-sectional views showing an example of a manufacturing process of the photoelectric conversion element 100. The photoelectric conversion element 100 can be manufactured mainly through the following steps. It should be noted that, for reference, Figure 2 (d) shows an example of a manufacturing process as an additional step when the inorganic semiconductor 107 is present between the (transparent) negative electrode layer 102 and the first layer 104 .

[0037] First, if Figure 2 As shown in (a), a substrate 110 having a negative electrode layer 102 for forming a photoelectric conversion layer 103 is prepared. The substrate 110 includes a supporting substrate 102A and a negative electrode layer 102 provided on the supporting substrate 102A. When light is taken from the substrate 110 side, the supporting substrate 102A and the negative electrode layer 102 have light transparency. The supporting substrate 10A is, for example, glass. The negative electrode layer 102 functions as a negative electrode layer, and an electrode member having transparent conductivity is used. A buffer layer (not shown) may be formed on one side of the negative electrode layer 102. The buffer layer may be formed by applying a solution of a material on the negative electrode layer 102 using a spin coating method or the like, and heating (drying) the solution. The heating is preferably performed at about 120 to 450° C. for about 10 to 60 minutes. The material coating conditions (coating time, etc.) are preferably adjusted so that the thickness of the buffer layer is, for example, about 1 to 100 nm.

[0038] Therefore, in the case where the inorganic semiconductor 107 exists between the (transparent) negative electrode layer 102 and the first layer 104 as in the above-mentioned "other device configuration", Figure 2 As shown in (b), by adding the following steps, an intermediate component having a desired structure is manufactured instead of Figure 2 The intermediate component shown in (a) can be used. First, an inorganic semiconductor layer 107 containing an inorganic semiconductor as a main component is formed on one side of the negative electrode layer 102 (if a buffer layer is present, the buffer layer is interposed). The method for forming the inorganic semiconductor layer 107 is not particularly limited. For example, the inorganic semiconductor layer 107 can be formed by vacuum evaporation, or by applying a dispersion of particles containing an inorganic semiconductor to the negative electrode layer 102 and heating it. It is preferable to adjust the conditions for applying the dispersion (coating time, etc.) so that the thickness of the first layer 104 is, for example, about 10 to 1000 nm, preferably about 50 to 500 nm. It should be noted that in the subsequent manufacturing process, it can replace Figure 2 The middle part shown in (a) is used Figure 2 The intermediate component shown in (b) undergoes the same steps (i.e., Figure 2 (c) to (f)) to manufacture the photoelectric conversion element 100.

[0039] Then, if Figure 2 As shown in (c), the surface of the substrate 110 is coated with a mixture of a raw material containing a perovskite structure 201 and an inorganic transition metal different from the central metal contained in the perovskite structure 201 (the first step). Specifically, the negative electrode layer 102 (it should be noted that, when there is an inorganic semiconductor layer 107, it is the inorganic semiconductor layer 107) is coated with a mixture of a raw material containing a perovskite structure and an inorganic transition metal 205 different from the central metal contained in the perovskite structure 201. Thus, the coating layer 120 is formed. The following is a description of the method for forming the coating layer 120.

[0040] First, the raw material of the perovskite structure and the inorganic transition metal (hereinafter sometimes referred to as the second layer inorganic transition metal) 205 different from the central metal contained in the raw material of the perovskite structure and contained in the perovskite structure 201 are mixed to obtain a mixture (mixing step). As the raw material of the perovskite structure, for example, there are compounds containing ions A and ions X (hereinafter sometimes referred to as the first compound) and compounds containing ions B and ions X (hereinafter sometimes referred to as the second compound). As compounds containing ions A and ions X, for example, CsCl, CsBr, CsI, MACl, MABr, MAI, FACl, FABr, FAI, etc. are mentioned. It should be noted that MA of MACl represents CH3NH3 + , FA means NH=CHNH2 + Examples of the compound containing ion B and ion X include PbCl2, PbBr2, PbI2, SnCl2, SnBr2, SnI2, and the like.

[0041] The second layer inorganic transition metal in the mixture may be contained in the form of a metal single substance, or in the form of a compound containing the second layer inorganic transition metal. The mixture preferably contains a compound containing the second layer inorganic transition metal. The compound containing the second layer inorganic transition metal is, for example, a compound containing the second layer inorganic transition compound and ion X (hereinafter sometimes referred to as the third compound). Examples of the compound containing the second layer inorganic transition compound and ion X include EuCl2, EuBr2, EuI2, YbCl2, YbBr2, YbI2, and the like.

[0042] As for the ratio of the first compound, the second compound, and the third compound in the entire mixture, for example, it is preferred to determine the ratio of each component so that the molar ratio of ion A, ion B, ion X, and the second layer inorganic transition metal (ion A: ion B: ion X: second layer inorganic transition metal) satisfies 1:1:3:0.3 to 1. For example, in order to make the second layer 105 a single atomic layer, it is preferred that the molar ratio of ion A, ion B, ion X, and the second layer inorganic transition metal in the entire mixture is 1:1:3:0.3 so that the final film composition ratio is 1:1:3:0.01. In this case, as a specific operation for making the second layer 105 a single atomic layer, for example, as in Example 1 described later, after forming a film using a solution formed by mixing ions B, ions X, and a second layer of inorganic transition metal (in the aforementioned mixture as a whole, the molar ratio of ions B: ions X: second layer of inorganic transition metal is 1:3:0.3), a solution containing ions A is applied (in the aforementioned mixture as a whole, the molar ratio of ions A is 1), thereby forming a two-layer coating layer. In addition, relative to the total mass of the mixture, the total content of the first compound, the second compound, and the third compound in the mixture as a whole is 90% by mass or more. As the aforementioned mixture as a whole can be composed only of the first compound, the second compound, and the third compound, the upper limit of the total content of the first compound, the second compound, and the third compound in the mixture as a whole is 100% by mass.

[0043] The mixture may be a solution containing a raw material of a perovskite structure and a second layer of inorganic transition metal, or may be a combination of a solution containing a portion of the raw material of a perovskite structure and a second layer of inorganic transition metal, and a solution containing another portion of the raw material of a perovskite structure. If it is a solution containing a raw material of a perovskite structure and a second layer of inorganic transition metal, or a solution containing a portion of the raw material of a perovskite structure and a second layer of inorganic transition metal and a solution containing another portion of the raw material of a perovskite structure, a coating layer 120 of uniform thickness can be formed using spin coating or the like. When the mixture is a solution, the solvent is a solvent that can dissolve the first compound, the second compound, and the third compound, and is not particularly limited. As solvents, dimethyl sulfoxide (DMSO), dimethylformamide (DMF), γ-butyrolactone, and the like can be cited. When the mixture is a solution, the total content of the first compound, the second compound, and the third compound is 90% by mass or more relative to the total mass of the mixture after drying. The entire mixture after drying may be composed only of the first compound, the second compound, and the third compound. Therefore, the upper limit of the total content of the first compound, the second compound, and the third compound in the entire mixture after drying is 100 mass %.

[0044] Next, the surface of the substrate 110 is coated with the mixture to form a coating layer 120 (coating process). The method for forming the coating layer 120 is not particularly limited. As the method for forming the coating layer 120, for example, spin coating, dipping, etc. can be cited. It is preferred to apply a solution containing a raw material of a perovskite structure and a second layer of inorganic transition metal, or a solution containing a part of the raw material of the perovskite structure and a second layer of inorganic transition metal and a solution containing another part of the raw material of the perovskite structure, and heat and dry, thereby forming the coating layer 120. Heating is preferably performed at about 40 to 100° C. for about 5 to 10 minutes. The conditions for applying the material (coating time, etc.) are adjusted in such a way that the thickness of the coating layer 120 becomes, for example, about 1 to 10 nm. The coating layer 120 can be a single layer containing all of the first compound, the second compound, and the third compound as a mixture as a whole. In addition, the coating layer 120 can be composed of two or more layers. An example in which the covering layer 120 is composed of two or more layers includes a layer containing the second compound and the third compound and a layer containing the first compound provided on the layer containing the second compound and the third compound.

[0045] Then, if Figure 2 As shown in (d), after the first step, a 1:1 layer arrangement is formed between the perovskite structure 201 and the second inorganic transition metal layer 205, thereby forming: a first layer composed of a plurality of particles or aggregates thereof or a thin film containing the perovskite structure 201 as a main component; and a second layer composed of a plurality of particles or aggregates thereof or a thin film containing the second inorganic transition metal 205 as a main component (second step). The method for forming a 1:1 layer arrangement between the perovskite structure 201 and the second inorganic transition metal layer 205 is not particularly limited. For example, it is preferable to heat the coating layer 120 to form: a first layer 104 composed of a plurality of particles or aggregates thereof or a thin film containing the perovskite structure 201 as a main component; and a second layer 105 composed of a plurality of particles or aggregates thereof or a thin film containing the second inorganic transition metal 205 as a main component (heating step). As the form of the first layer 104, a thin film is preferred. As the form of the second layer 105, a thin film is preferred. By heating, the first compound and the second compound form a perovskite structure 201. The first layer 104 is formed by the formation of the perovskite structure 201. At this time, simultaneously with the formation of the first layer 104, the second layer inorganic transition metal 205 is segregated on the surface of the first layer 104, thereby forming the second layer 105, and forming a 1:1 layer arrangement between the perovskite structure 201 and the second layer inorganic transition metal 205. The second layer 105 is preferably a monoatomic layer.

[0046] The heating temperature is not particularly limited as long as the perovskite structure 201 can be formed and the second inorganic transition metal layer 205 is segregated on the surface of the first layer 104. The heating temperature is, for example, 200°C to 300°C. The heating time is not particularly limited as long as the perovskite structure 201 can be formed and the second inorganic transition metal layer 205 can be segregated on the surface of the first layer 104. The heating time is, for example, preferably more than 5 minutes. More preferably, for example, more than 5 minutes and less than 60 minutes can be cited. More preferably, for example, more than 20 minutes and less than 30 minutes can be cited.

[0047] Then, if Figure 2 (e) In this way, a third layer 106 composed of a plurality of particles or aggregates thereof or a thin film and containing an organic ligand 206 as a main component is formed on the second layer 105. As the form of the third layer 106, a monomolecular thin film is preferably used. At this time, the organic ligand 206 is coordinately bonded to the second layer of inorganic transition metal 205 on the second surface 105b opposite to the surface 105a of the second layer 105 in contact with the first layer 104, thereby forming an organic metal complex layer 108 obtained from an organic metal complex (third process). The method for making the organic ligand 206 coordinately bonded to the second layer of inorganic transition metal 205 is not particularly limited. For example, a solution containing the organic ligand 206 is applied to the second layer 105 (application process) and maintained for a certain period of time (for example, 30 seconds). After being maintained, it can be dried to form the organic metal complex layer 108. It is preferred to remove the organic ligand 206 that does not form the organic metal complex 208. The method for removing the organic ligand 206 is not particularly limited. For example, the organic ligand 206 that has not formed the organic metal complex 208 can be removed by washing the substrate 110 with an organic solvent or the like.

[0048] Finally, if Figure 2 As shown in (f), by forming the positive electrode layer 101 on the third layer 106, more specifically, on the layer containing the organic ligand, the photoelectric conversion element 100 of this embodiment can be obtained. The method for forming the positive electrode layer 101 is not particularly limited. The positive electrode layer 101 can be formed, for example, by vacuum deposition or by coating a conductive paste.

[0049] (Band structure) Figure 3 (a) to (d) are diagrams for explaining the operating principle (action) of the photoelectric conversion element 100 according to this embodiment, and respectively show the energy band structure of each layer before irradiation with light, immediately after irradiation with light, and after a predetermined time has passed since irradiation with light.

[0050] In the state where no light is irradiated, the energy level of the conduction band of the organic metal complex layer 108 is higher than the Fermi level of the positive electrode layer 101 on the positive electrode layer 101 side, such as Figure 3 As shown in (a), the current from the positive electrode layer 101 to the negative electrode layer 102 is blocked.

[0051] When the photoelectric conversion element 100 is irradiated with light, the perovskite structure constituting the first layer 104 absorbs the light to generate electrons and holes. Figure 3 As shown in (b), electrons move to the conduction band and holes move to the valence band.

[0052] At this time, the energy level E of the conduction band of the first layer 104 is c2 , the LUMO energy level E of the conduction band of the organic metal complex layer 108 c3 In E c3 >E c2 relationship, so Figure 3 As shown in (c), the electrons generated in the first layer 104 and moved to the conduction band of the layer move to the conduction band of the organic metal complex layer 108 which is in a lower energy state. It should be noted that Figure 3 E in c3A represents the LUMO energy level of the conduction band of the second layer 105, E c3B represents the LUMO energy level of the conduction band of the third layer 106. Wherein, the energy level E of the organic metal complex layer 108 c3 Set to E c3A and E c3B . It should be noted that when the inorganic semiconductor 107 is present between the (transparent) negative electrode layer 102 and the first layer 104, the energy level E of the conduction band of the inorganic semiconductor layer 107 is c1 , the energy level E of the conduction band of the first layer 104 c2 , the LUMO energy level E of the conduction band of the organic metal complex layer 108 c3 In E c3 >E c2 >E c1 , so the electrons generated in the first layer 104 and moved to the conduction band of the layer move to the conduction band of the organic metal complex layer 108 which becomes a lower energy state, and then move to the conduction band of the inorganic semiconductor layer 107 which becomes a lower energy state. It should be noted that Figure 3 E in c3A represents the LUMO energy level of the conduction band of the second layer 105, E c3B represents the LUMO energy level of the conduction band of the third layer 106. Here, the LUMO energy level E of the organic metal complex layer 108 is c3 Set to E c3A and E c3B .

[0053] On the other hand, the energy level E of the valence band of the first layer 104 v2, the HOMO energy level E of the valence band of the organic metal complex layer 108 v3 Satisfy E v2 >E v3 , so if Figure 3 As shown in (c), holes generated in the first layer 104 and moved to the valence band are captured by the valence band of the first layer 104 which is in a relatively high energy state (low for holes) compared to the organic metal complex layer 108 . It should be noted that when the inorganic semiconductor 107 is present between the (transparent) negative electrode layer 102 and the first layer 104, the energy level E of the valence band of the inorganic semiconductor layer 107 is v1 , the energy level E of the valence band of the first layer 104 v2 , the HOMO energy level E of the valence band of the organic metal complex layer 108 v3 Satisfy E v2 >E v1 、E v2 >E v3 Therefore, holes generated in the first layer 104 and transferred to the valence band are captured by the valence band of the first layer 104 which is in a relatively high energy state (low for holes) compared to the inorganic semiconductor layer 107 and the organic metal complex layer 108 .

[0054] Due to the influence of the holes that are captured and concentrated (positive potential), the potential energy of the electrons is reduced near the valence band of the first layer 104, and the energy level of the conduction band is reduced. The closer to the first layer 104 that captures the holes, the more significantly the energy level of the conduction band is reduced, so the LUMO energy level of the conduction band of the organic metal complex layer 108 becomes lower on the first layer 104 side, and the positive electrode layer side becomes a sharp shape. Therefore, for the electrons present in the positive electrode layer 101, the energy barrier of the organic metal complex layer 108 becomes thinner, and tunneling can be performed to the negative electrode layer side. That is, it is believed that with respect to the majority of electrons on the positive electrode side that are blocked by the energy barrier of the organic metal complex layer 108 (electrons in a state where light is not irradiated), when the photoelectric conversion element 100 is irradiated with light, it is tunneled (transmitted) from the thinned energy barrier and flows into the negative electrode side, thereby being able to achieve a significant amplification of the current directly generated by the irradiated light.

[0055] The total thickness of the second layer 105 and the third layer 106 is preferably greater than the thickness of a monomolecular layer of the organic metal complex 208. The second layer 105 and the third layer 106 preferably form a monomolecular layer of the organic metal complex 208. The total thickness of the second layer 105 and the third layer 106 is preferably less than 10 nm. When the total thickness of the second layer 105 and the third layer 106 is thicker than 10 nm, the energy barrier becomes too thick, and a sufficient tunneling probability cannot be obtained, and the amplification of the photocurrent in the photoelectric conversion element 100 will be hindered. In addition, if the second layer 105 and the third layer 106 are thinner than the monomolecular layer of the organic metal complex 208, the tunneling current will flow even when no light is irradiated and the energy band is not bent, and the light detection function of the photoelectric conversion element 100 loses its meaning.

[0056] (Light detection method) The light detection method using the photoelectric conversion element 100 includes the following steps: the photoelectric conversion layer 103 receives visible light and / or near-infrared light, thereby causing a current to flow between the negative electrode layer 102 and the positive electrode layer 101 , and the visible light and / or near-infrared light is detected by measuring the current. The current generated by receiving light can be measured by a known method. 5 The absorbed light is amplified by an order of magnitude, so even weak light can be easily detected.

[0057] As described above, the photoelectric conversion element 100 involved in this embodiment is irradiated with light in a state driven by applying a voltage between the positive electrode layer 101 and the negative electrode layer 102, and a photocurrent can be generated and amplified and output. In addition, since the photoelectric conversion element 100 can be driven at a low voltage, it can be output in a state where noise generation is suppressed, and the measurement accuracy of the photocurrent can be improved. Therefore, a photoelectric conversion device such as a light sensor and a camera equipped with the photoelectric conversion element 100 can achieve high-power amplification even at a driving voltage of, for example, less than 1v, so that a high bias (i.e., a high-voltage driving circuit) is not required, and the product can be compact. In addition, with respect to the photoelectric conversion element 100, the perovskite structure 201 and the second layer of inorganic transition metal 205 form a 1-to-1 layer arrangement, so that the response speed can be improved. In addition, the photoelectric conversion element 100 of this embodiment can easily change the shape of the energy level by adjusting the combination and composition of the materials of each layer, so that the response sensitivity can be improved, and in addition, the light of the desired wavelength can also be selectively absorbed.

[0058] The photoelectric conversion element 100 may include a buffer layer (not shown) between the negative electrode layer 102 and the photoelectric conversion layer 103. The energy level Ecb of the conduction band of the buffer layer is between the energy level of the negative electrode layer 102 and the energy level of the conduction band of the first layer 104 (it should be noted that it is the inorganic semiconductor layer 107 when there is an inorganic semiconductor layer 107). As constituent materials of the buffer layer, for example, europium oxide (Eu2O3), titanium oxide, tin oxide, etc. can be cited. Example

[0059] The effects of the present invention will be further clarified by way of examples. It should be noted that the present invention is not limited to the following examples, and can be implemented with appropriate modifications within the scope of the gist thereof.

[0060] (Example 1) The photoelectric conversion element of Example 1 was produced under the following conditions.

[0061] First, a component containing antimony-doped tin oxide (ATO) as a component used as a negative electrode layer including a substrate is prepared. 200 μl of a 0.18M ethanol solution of diisopropoxydiacetylacetonate titanium is spin-coated on one side of the component at a rotation speed of 3000 rpm. Next, the mixed solution spin-coated on the component is heated at 500° C. for 30 minutes, thereby forming a buffer layer substantially made of a dense film of titanium oxide (TiO2).

[0062] Next, 150 μl of a dimethyl sulfoxide (DMSO) solution of 1.25M lead iodide (PbI2) and 0.375M europium chloride (EuCl2) is dripped onto the surface of the buffer layer (the surface on the opposite side of the negative electrode layer) and spin-coated at 2000 rpm. Next, the spin-coated component is heated at 150°C for 30 minutes (process A). 100 μl of an anhydrous methanol solution of 0.07M cesium chloride (CsCl2) is dripped onto the spin-coated surface of the component and spin-coated at 3000 rpm. By performing the operations in sequence, a coating layer having a two-layer structure is formed on the component (process B). Next, the component having the coating layer is heated at 250°C for 5 minutes. This operation (process A and process B) is repeated 5 times to form a first layer of a perovskite structure and a second layer of an inorganic transition metal segregated on the first layer that is different from the central metal contained in the perovskite structure.

[0063] Next, 200 μl of an isopropyl alcohol (IPA) solution containing 1-phenylethylamine at a concentration of 20 mM was dripped onto the surface of the second layer for 30 seconds. Then, spin coating was performed at a rotation speed of 3000 rpm. Next, the substrate was heated at 100° C. for 15 minutes, thereby forming a third layer having 1-phenylethylamine as the main component.

[0064] Finally, a positive electrode layer (Ag) was formed on the opposite side of the negative electrode layer through the stacked body including the first layer, the second layer, and the third layer in contact with the third layer, thereby obtaining the photoelectric conversion element of Example 1. With respect to the photoelectric conversion element obtained in this manner, when the energy level is calculated based on the combination of the raw materials used, in the conduction band, the LUMO energy level of the conduction band of the organic metal complex layer of Example 1 is higher than the energy level of the conduction band of the first layer, and in the valence band, the energy level of the valence band of the first layer of Example 1 is higher than the HOMO energy level of the valence band of the organic metal complex layer.

[0065] (Comparative Example 1) The photoelectric conversion element of Comparative Example 1 was produced under the following conditions.

[0066] First, as a component used as a negative electrode layer containing a substrate, a component containing antimony-doped tin oxide (ATO) as a component is prepared. On the surface of the component, 200 μl of an ethanol (C2H5OH) solution containing europium chloride hydrate (EuCl3·6H2O) at a concentration of 10 mM is spin-coated at a speed of 3000 rpm. The spin-coated substrate is heated at 120°C for 10 minutes, and then heated at 450°C for 1 hour, thereby forming a buffer layer of europium oxide (Eu2O3).

[0067] Next, 120 μl of a mixture of titanium oxide (TiO2) slurry (PST18NR, manufactured by JGC Catalysts & Chemicals Co., Ltd.) and ethanol at a weight ratio of 1:3.5 was dropped onto the surface of the buffer layer and spin-coated at 6000 rpm. Next, the spin-coated substrate was heated at 120°C for 10 minutes and at 450°C for 1 hour, thereby forming an inorganic semiconductor layer composed of a plurality of titanium oxide particles.

[0068] Next, 100 μl of a mixed solution of dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) containing lead iodide (PbI2) and methylammonium at a concentration of less than 0.5 M was dropped onto the substrate and spin-coated at a speed of 5000 rpm. Next, the spin-coated substrate was heated at 40°C for 5 minutes, at 70°C for 5 minutes, and at 100°C for 10 minutes, thereby forming a first layer with a perovskite structure (CH3NH3PbI3) as the main component on the inorganic semiconductor layer.

[0069] After the first layer was formed, 100 μl of an isopropyl alcohol (IPA) solution containing europium chloride (EuCl3) at a concentration of 5 mM was dropped onto the substrate and spin-coated at 5000 rpm. The spin-coated substrate was then heated at 100° C. for 15 minutes to form a second layer containing europium as the main component on the first layer.

[0070] After the second layer is formed, 200 μl of an isopropyl alcohol (IPA) solution containing terpyridine (2,2':6',2"-terpyridine) at a concentration of 20 mM is dripped onto the surface of the layer having europium as the main component and maintained for 30 seconds. Then, spin coating is performed at a rotation speed of 3000 rpm. Next, the substrate is heated at 100°C for 15 minutes to form a third layer having terpyridine as the main component.

[0071] Finally, a positive electrode layer (Ag) was formed on the side opposite to the negative electrode layer and in contact with the third layer via the stacked body including the inorganic semiconductor layer, the first layer, the second layer, and the third layer, thereby obtaining a photoelectric conversion element of Comparative Example 1.

[0072] (Example 2) The photoelectric conversion element of Example 2 is prepared by the following method. As a component used as a negative electrode layer including a substrate, a component containing antimony-doped tin oxide (ATO) as a component is prepared. On one side of the component, 120 μl of a mixed solution containing titanium oxide (TiO2) slurry (PST18NR, manufactured by JGC Catalysts & Chemicals Co., Ltd.) and ethanol in a weight ratio of 1:3.5 is spin-coated at a rotation speed of 6000 rpm. Next, the mixed solution spin-coated on the substrate is heated at 120°C for 10 minutes and at 450°C for 1 hour, thereby forming a porous film containing multiple particles substantially obtained from titanium oxide.

[0073] Next, 100 μl of a mixed solution of 0.5M lead iodide (PbI2) and 0.5M methylammonium, dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) was dropped onto the surface of the porous membrane (the surface on the opposite side of the negative electrode layer) and spin-coated at 5000 rpm. Next, the spin-coated component was heated at 40°C for 5 minutes, at 70°C for 5 minutes, and at 100°C for 10 minutes, thereby forming a first layer with a perovskite structure (CH3NH3PbI3) as the main component on the component.

[0074] Next, 100 μl of an isopropyl alcohol (IPA) solution containing europium chloride (EuCl3) at a concentration of 1 mM was dripped onto the surface of the first layer (the spin-coated surface on the opposite side of the negative electrode layer), and spin-coated at a rotation speed of 5000 rpm. Next, the spin-coated component was heated at 100° C. for 15 minutes, thereby forming a second layer with europium as the main component on the first layer, and the photoelectric conversion element of Example 2 was produced.

[0075] (Example 3) The photoelectric conversion element of Example 3 was produced under the same conditions as in Example 2 except that an isopropyl alcohol (IPA) solution containing europium chloride (EuCl 3 ) at a concentration of 5 mM was used.

[0076] (Example 4) The photoelectric conversion element of Example 4 was produced under the same conditions as in Example 2 except that an isopropyl alcohol (IPA) solution containing europium chloride (EuCl 3 ) at a concentration of 7.5 mM was used.

[0077] (Example 5) The photoelectric conversion element of Example 5 was produced under the same conditions as in Example 2 except that an isopropyl alcohol (IPA) solution containing europium chloride (EuCl 3 ) at a concentration of 10 mM was used.

[0078] (Confirmation of perovskite structure and layer arrangement of inorganic transition metals) In order to confirm that the perovskite structure and the inorganic transition metal different from the central metal contained in the perovskite structure form a 1 to 1 layer arrangement, the following steps are used for operation. By observing the cross section of the photoelectric conversion element 100 using SEM, or measuring the surface potential using a scanning probe microscope, it is possible to confirm that the perovskite structure and the inorganic transition metal different from the central metal contained in the aforementioned perovskite structure exist as a layer with a 1 to 1 layer arrangement with a thickness of several nm. In addition, it is also possible to confirm by measuring the presence and binding state of inorganic transition metal ions present in a few nm on the surface using X-ray photoelectron spectroscopy (XPS).

[0079] (Confirmation of Formation of Organometallic Complex Layer) In order to confirm the formation of an organic metal complex, the following steps are used. By observing the cross section of the photoelectric conversion element 100 with a TEM, it can be confirmed that the organic metal complex formed by the coordination bonding of the organic ligand and the inorganic transition metal forms a layer. In addition, the formation of the organic metal complex layer can be confirmed using X-ray photoelectron spectroscopy (XPS) and FT-IR.

[0080] (Response speed) For the photoelectric conversion element of Example 1, light irradiation conditions were set at a predetermined time point, and the photocurrent generated in the photoelectric conversion element was measured. The voltage applied between the positive electrode layer and the negative electrode layer was -0.5 V. The wavelength, irradiance, and irradiation interval (frequency) of the light irradiated to the photoelectric conversion element were set to 550 nm, 1 mW / cm 2 , 1500Hz. Figure 4 The graphs are graphs showing the measurement results corresponding to the photoelectric conversion element of Example 1. In the graph, the horizontal axis represents the elapsed time (s), and the vertical axis represents the photocurrent (A / cm 2 ).

[0081] according to Figure 4 The photocurrent in the photoelectric conversion element of Example 1 instantly rises to a maximum value (maximum value: about 1 A / cm 2 ). The response speed of the photoelectric conversion element of Example 1 is 14 μs. On the other hand, in the case of Comparative Example 1, it is 30 to 70 μs. The gain of the photoelectric conversion element of Example 1 is as high as 1600.

[0082] (Evaluation of potential) Next, the relationship between the amount of the second layer of inorganic transition metal 205 on the surface of the first layer 104 and the hole capture efficiency was studied. Specifically, a scanning probe microscope (SPM-9700HT manufactured by Shimadzu Corporation) was used to measure the surface potential of the photoelectric conversion elements of Examples 2 to 4 produced by changing the concentration of Eu. As for the cantilever, a Pt-coated cantilever was used. The surface potential was measured after light irradiation (irradiation condition 1 mW / cm 2 The test was conducted in the case where light irradiation was performed (i.e., a test area showing the characteristics and effects of the present invention) and in the case where light irradiation was not performed (i.e., a control test area showing the characteristics and effects of the present invention).

[0083] Figure 5 The surface potential measurement results are shown. It should be noted that a potential level bar (lower limit 0.2V to upper limit 0.5V) is shown on the right side of the potential image. Among them, in the potential level bar, for values ​​higher than its center value (0.35V), the darker part of the shade indicates a high potential. On the other hand, for values ​​lower than the center value (0.35V) of the potential level bar, the lighter part of the shade indicates a low potential. In addition, by comparing the shades in the potential level bar with the shades in the potential image, the detailed distribution and state of the potential level in the potential image can be understood. In the absence of light irradiation, no significant changes were observed in any potential image, and its potential was roughly displayed as a value lower than the center value of the potential level bar in the overall potential image, but in the case of light irradiation, up to 7.5mM, the concentrated portion of the overall potential image increased, and its potential was uniformly displayed as a value higher than the center value of the potential level bar in the overall potential image. This shows that holes can be captured efficiently by coating the surface with Eu. However, if it exceeds 10mM, on the contrary, the concentrated portion of the overall potential image decreases, and its average potential level is lower than the average potential level in the case of 7.5mM. This shows that if the thickness of the second layer becomes thicker, the efficiency of hole capture decreases. It is speculated that the surface of the first layer 104 is coated at a single atomic layer level up to 7.5mM. Based on the above results, it is inferred that the photoelectric conversion element of Example 1 can efficiently capture holes, thereby improving the response speed.

[0084] In the above potential evaluation measurement, the surface potential measurement results of each sample observed using a scanning probe microscope (SPM-9700HT manufactured by Shimadzu Corporation) are shown in FIG. Figure 5 The surface potential measurement result is a texture display obtained by superimposing a surface potential image on a surface shape image (i.e., height image) observed using a scanning probe microscope (SPM-9700HT manufactured by Shimadzu Corporation) under the conditions of "with light irradiation" or "without light irradiation" with the aforementioned "part formed of a first layer having a perovskite structure and a second layer of an inorganic transition metal different from the central metal contained in the perovskite structure and segregated on the first layer" (see paragraph

[0085] ). When the Eu concentration is 7.5 mM, it is uniformly displayed as a value higher than the center value (0.35 V) of the potential level bar in the entire potential image, so it can be indirectly confirmed that at the above-mentioned Eu concentration, at the position circumscribed to the octahedral structure of the unit unit constituting the perovskite structure 201, the above-mentioned perovskite structure 201 and the inorganic transition metal 205 form a one-to-one layer arrangement. It should be noted that, when the Eu concentration is 5 mM, the values ​​higher than the center value (0.35 V) of the potential level bar are sparsely present in the entire potential image and lack uniformity, but in some areas, it can still be confirmed that the aforementioned perovskite structure 201 and the inorganic transition metal 205 form a 1 to 1 layer arrangement at the position circumscribed to the octahedral structure of the unit unit constituting the perovskite structure 201. On the other hand, when the Eu concentration is 10 mM, the values ​​higher than the center value (0.35 V) of the potential level bar decrease, and the average potential level is lower than the average potential level at 7.5 mM, so it can be confirmed that the aforementioned perovskite structure 201 and the inorganic transition metal 205 do not properly form a 1 to 1 layer arrangement at the position circumscribed to the octahedral structure of the unit unit constituting the perovskite structure 201. From this, it can be seen that, for a sample formed by adjusting the amount of an inorganic transition metal different from the central metal contained in the perovskite structure, if the texture display formed by superimposing a surface potential image on a surface shape image observed using a scanning probe microscope is confirmed, it can be confirmed whether the aforementioned perovskite structure 201 and the inorganic transition metal 205 properly form a one-to-one layer arrangement.

[0086] According to the above test results, it can be confirmed that the photoelectric conversion element (photoelectric conversion device) of the present invention has an excellent response speed by forming a 1:1 layer arrangement of the perovskite structure and the inorganic transition metal different from the central metal contained in the perovskite structure 201. In addition, an excellent capture effect of holes based on the second layer (i.e., more efficient capture) was confirmed. Industrial Applicability

[0087] The photoelectric conversion element of the present disclosure has high efficiency and high sensitivity for weak optical signals while suppressing environmental load to a low level, and therefore has high industrial applicability. Description of Reference Numerals

[0088] 100 photoelectric conversion element, 101 positive electrode layer, 102 negative electrode layer, 103 photoelectric conversion layer, 104 first layer, 105 second layer, 106 third layer, 107 inorganic semiconductor layer, 108 organic metal complex layer, 201 perovskite structure, 205 second layer inorganic transition metal, 206 organic ligand, 208 organic metal complex

Claims

1. A photoelectric conversion element, characterized in that: As a photoelectric conversion layer, it has the following in order: A first layer composed of a plurality of particles containing a perovskite structure as a main component, or an aggregate or a thin film thereof; A second layer composed of a plurality of particles containing an inorganic transition metal as a main component, or an aggregate or a thin film thereof; and The third layer is composed of a plurality of particles or aggregates or thin films containing an organic ligand as a main component, The inorganic transition metal of the second layer is different from the central metal contained in the perovskite structure, At the boundary surface between the first layer and the second layer, the perovskite structure and the inorganic transition metal of the second layer form a one-to-one layer arrangement, At the interface between the second layer and the third layer, the inorganic transition metal in the second layer and the organic ligand in the third layer together form an organic metal complex layer obtained from an organic metal complex.

2. The photoelectric conversion element according to claim 1, wherein In the conduction band, the LUMO energy level of the conduction band of the organic metal complex layer is higher than the energy level of the conduction band of the first layer, and In the valence band, the energy level of the valence band of the first layer is higher than the HOMO energy level of the valence band of the organic metal complex layer.

3. The photoelectric conversion element according to claim 1, wherein The second layer is a layer in which the inorganic transition metal is segregated on the surface of the first layer.

4. The photoelectric conversion element according to claim 1, wherein The second layer is a single atomic layer of the inorganic transition metal.

5. The photoelectric conversion element according to claim 1, wherein The organic ligand is α-methylbenzylamine or terpyridine.

6. The photoelectric conversion element according to claim 5, wherein The central metal contained in the perovskite structure is lead, the inorganic transition metal of the second layer is europium, the inorganic transition metal of the second layer constituting the organic metal complex is europium, and the organic ligand constituting the organic metal complex is α-methylbenzylamine or terpyridine.

7. The photoelectric conversion element according to any one of claims 1 to 6, wherein The perovskite structure is a compound represented by the formula CH3NH3PbI3.

8. A photoelectric conversion device, characterized in that The photoelectric conversion element according to claim 1 comprises: A negative electrode layer is stacked on the opposite side of the second layer via the first layer, and A photoelectric conversion element in which a positive electrode layer is stacked on the opposite side of the second layer via the third layer.

9. A method for detecting light, characterized in that: The process includes the following steps: In the photoelectric conversion device according to claim 8, the photoelectric conversion layer receives visible light and / or near-infrared light, thereby causing current to flow between the negative electrode layer and the positive electrode layer. The visible light and / or the near-infrared light is detected by measuring the current.

10. A method for manufacturing a photoelectric conversion element, characterized in that: include: A first step is to coat the surface of a substrate with a mixture, wherein the mixture includes a raw material for a perovskite structure and an inorganic transition metal different from a central metal contained in the raw material for the perovskite structure and in the perovskite structure; A second step, after the first step, by forming a one-to-one layer arrangement between the perovskite structure and the inorganic transition metal, thereby forming a first layer consisting of a plurality of particles or aggregates or thin films containing the perovskite structure as a main component, and a second layer consisting of a plurality of particles or aggregates or thin films containing the inorganic transition metal as a main component; and In the third step, after the second step, an organic ligand is coordinated and bonded to the inorganic transition metal on the second surface of the second layer opposite to the surface in contact with the first layer, thereby forming an organic metal complex layer obtained from the organic metal complex.

11. The method for manufacturing a photoelectric conversion element according to claim 10, wherein: In the conduction band, the LUMO energy level of the conduction band of the organic metal complex layer is higher than the energy level of the conduction band of the first layer, and In the valence band, the energy level of the valence band of the first layer is higher than the HOMO energy level of the valence band of the organic metal complex layer.

12. The method for manufacturing a photoelectric conversion element according to claim 10, wherein: In the second step, the second layer is formed by segregating the inorganic transition metal on the surface of the first layer.

13. The method for manufacturing a photoelectric conversion element according to claim 10, wherein: The second layer is a single atomic layer of the inorganic transition metal.

14. A method for manufacturing a photoelectric conversion element, characterized in that: include: a mixing step of mixing a raw material of a perovskite structure and an inorganic transition metal different from a central metal contained in the raw material of the perovskite structure and in the perovskite structure, thereby obtaining a mixture; A coating step of coating the surface of the substrate with the mixture to form a coating layer; A heating step of heating the coating layer after the coating step to form a first layer consisting of a plurality of particles or aggregates or thin films containing the perovskite structure as a main component, and a second layer consisting of a plurality of particles or aggregates or thin films containing the inorganic transition metal as a main component; and After the heating step, a step of applying a solution containing an organic ligand on the surface of the second layer opposite to the surface in contact with the first layer.

Citation Information

Patent Citations

  • Manufacturing method of roux

    JP2022130971A

  • Photoelectric conversion element, photoelectric conversion device, photoelectric conversion element precursor, light detection method, and production method for photoelectric conversion element

    WO2020162317A1